Analisis Ekonomi-Hukum Terhadap Larangan Impor Barang Bekas (Thrifting) dan Dampaknya Terhadap UMKM - Daniela Marito Br Tambunan; Dini Manurung; Sri Handayani (Equivalent : Journal of Economic, Accounting and Management, 2025)
Abstract : Thrifting phenomenon has become a trend in Indonesia. Thrifting is an activity of buying second-hand or used goods that are sold at relatively cheap prices. This study was conducted to analyze Thrifting with the import ban policy and its impact on MSMEs in Indonesia. This study uses a literature study method involving a literature review. The results of the study are seen from the low price of imported goods (Thrifting) compared to the price of local goods, this directly affects the local market which is unable to compete with the price of imported goods. The government prohibits the import of used goods which aims to protect the community in terms of health and also to protect the local industry from the onslaught of imported used goods. However, even though the government has set a ban on the import of used goods, the smuggling of these goods is still ongoing. Abstrak : Fenomena Thrifting telah menjadi tren di Indonesia. Thrifting merupakan kegiatan membeli barang second atau bekas yang di jual dengan harga relatif murah. Penelitian ini dilakukan untuk menganalisis Thrifting dengan kebijakan larangan impor dan dampak nya terhadap UMKM di Indonesia. Penelitian ini menggunakan metode studi literatur yang melibatkan tinjauan Pustaka. Hasil penelitian dilihat dari rendahnya harga barang impor (Thrifting) disbanding harga barang lokal, hal ini secara langsung mempengaruhi pasar lokal yang tidak mampu bersaing dengan harga barang impor. Pemerintah melarangan adanya impor barang bekas yang bertujuan untuk melindungi Masyarakat dari segi Kesehatan dan juga untuk melindungi industri lokal dari gempuran barang bekas impor. Namum meskipun pemerintah telah menetapkan larangan impor barang bekas penyelundupan barang ini masih berlangsung.